2020
DOI: 10.1016/j.neuropsychologia.2017.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Preferential processing of task-irrelevant beloved-related information and task performance: Two event-related potential studies

Abstract: People who are in love have better attention for beloved-related information, but report having trouble focusing on other tasks, such as (home)work. So, romantic love can both improve and hurt cognition. Emotional information is preferentially processed, which improves task performance when the information is task-relevant, but hurts task performance when it is task-irrelevant. Because beloved-related information is highly emotional, the effects of romantic love on cognition may resemble these effects of emoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Taken together, these studies suggest that an EPN for the beloved occurs with both fast and slow stimulus presentation. In three of these four analyses, there was no EPN for friend (vs. stranger) pictures [50,56], which suggests that the EPN for the beloved is not the result of familiarity or positive valence. The effect of beloved stimuli on the EPN suggests that the beloved captures early attention that is relatively resource-independent, which probably reflects the evolutionary significance of the beloved due to romantic love playing an important role in reproduction [61].…”
Section: Early Posterior Negativity (Epn)mentioning
confidence: 91%
See 2 more Smart Citations
“…Taken together, these studies suggest that an EPN for the beloved occurs with both fast and slow stimulus presentation. In three of these four analyses, there was no EPN for friend (vs. stranger) pictures [50,56], which suggests that the EPN for the beloved is not the result of familiarity or positive valence. The effect of beloved stimuli on the EPN suggests that the beloved captures early attention that is relatively resource-independent, which probably reflects the evolutionary significance of the beloved due to romantic love playing an important role in reproduction [61].…”
Section: Early Posterior Negativity (Epn)mentioning
confidence: 91%
“…Importantly, this love effect on the P3 occurred regardless of the target/distractor status of the pictures, which implies that the enhanced attention for the beloved occurred regardless of the instruction to pay attention to the beloved or not. In two other studies [56], participants who were in love performed short-term memory tasks with neutral shapes while taskirrelevant face pictures of the beloved, friend, and strangers were presented. Participants were informed that the faces were task-irrelevant (study 1) or were instructed to ignore them (study 2).…”
Section: Task Paradigmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since infatuation is a more arousing state than attachment (Gonzaga et al, 2006), a different approach is to correlate the LPP amplitude difference with arousal rating differences between beloved and friend. Although this correlation was significant in one study (Study 2 of Langeslag & Van Strien, 2020), it was not significant in two other studies (Langeslag et al, 2015; Study 1 of Langeslag & Van Strien, 2020). So, it is as of yet unclear if the LPP in response to the beloved is sensitive to individual differences in subjective arousal, infatuation, and/or attachment.…”
mentioning
confidence: 84%
“…These neurons form part of a neural pathway that processes visual information from the retina via the superior colliculus, allowing for fast detection of threatening stimuli (Morris, Öhman, & Dolan, 1999;Tamietto & de Gelder, 2010). Several electroencephalographic (EEG) studies on humans have provided evidence in support of the Snake Detection Theory (He, Kubo, & Kawai, 2014;Grassini et al, 2019;Grassini, Holm, Railo, & Koivisto, 2016;Grassini, Railo, Valli, Revonsuo, & Koivisto, 2018;Langeslag & van Strien, 2017;Van Strien, Christiaans, Franken, & Huijding, 2016;Van Strien, Eijlers, Franken, & Huijding, 2014a;Van Strien, Franken, & Huijding, 2014b;Van Strien & Isbell, 2017). These have shown that images of snakes specifically modulate an early/intermediate event-related potential (ERP) component-the Early Posterior Negativity (EPN, a negative deflection around 225-300 from stimulus onset).…”
Section: Snakes and Evolutionary Priorities In Visual Perceptionmentioning
confidence: 99%